Effectiveness of Problem Based Learning and Value Clarification Technique in History Learning to Improve Moral Awareness - Piki Setri Pernantah (Jurnal Ilmu Sosial Mamangan, 2020)
Moral awareness is one of the students affective skill that able to become a successful indicator of history learning. It causes history learning has a purpose in building students attitude. The study intended to know the effectiveness of learning history by using problem based learning and value clarification technique for improving students moral awareness. The research method used experimental quasi. Its sample was students of XI Social Science SMAN 2 Padang, consisting of twenty nine students in experimental class and twenty eight students in control class. Based on statistical measurement result showed the mean of post-test score in experimental class was 127 and control class was 111.25. Hypothesis test result by using t test independent samples, was gotten t arithmetic value of 1.749 with significant level of 0,000 < 0,025, thus H0 rejected. Furthermore, it could be concluded that problem based learning and value clarification technique effective to improve students moral awareness of history learning in high school.